2004
DOI: 10.1055/s-2004-814198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Undernutrition on Serum and Testicular Testosterone Levels and Sexual Function in Adult Rats

Abstract: The aim of this study was to evaluate testosterone concentrations, sexual behavior, and androgen receptor protein level in the testes of rats submitted to protein- and energy-restricted diets during 30 days. Adult male Wistar rats were assigned to one of the following groups: (C) control, diet with 23% of protein; (PR) protein-restricted, diet with 8% of protein; (ER) energy-restricted, diet with 23% of protein in restricted quantities. Mount number, ejaculation latencies and copulatory efficiency were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Why the Npr2 cn-2J/cn-2J mice do not suffer from these GI problems is not clear, but may depend on the respective genetic backgrounds. These conclusions about the importance of nutrition are consistent with reports on the role of nutrition in growth and development of the reproductive system [16]; moreover, dietary restriction is known to impact negatively on testicular volume, weight and function [18,19]. …”
Section: Discussionsupporting
confidence: 89%
“…Why the Npr2 cn-2J/cn-2J mice do not suffer from these GI problems is not clear, but may depend on the respective genetic backgrounds. These conclusions about the importance of nutrition are consistent with reports on the role of nutrition in growth and development of the reproductive system [16]; moreover, dietary restriction is known to impact negatively on testicular volume, weight and function [18,19]. …”
Section: Discussionsupporting
confidence: 89%
“…Secretion of testosterone is probably impaired due to excessive oxidative stress and the degeneration of Leydig cells [46]. Metabolites of testosterone reciprocally depress FSH and LH secretion [47].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that caloric restriction might result in central hypogonadism 29 and induce significant decreases in testis and epididymis weights, serum and testicular testosterone concentrations as well as AR protein levels in the testis of rats. 30 That refeeding after the caloric restriction is able to elevate the testosterone level mildly to some extent but not recover completely and promptly, 31 might be an important reason for the inappropriate normal LH levels and reduced testosterone levels in male CUFA humans and rats in the present study. 32,33 Additionally, neuronal insulin receptor knockout mice become insulin resistant and also have a reduction in LH concentrations and low testosterone concentrations, 34 implying that the IR of the central system during refeeding after caloric restriction might also be a contribution to hypogonadotropism in male CUFA rats.…”
Section: Discussionmentioning
confidence: 56%